2002
DOI: 10.1063/1.1521726
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and rotationally inelastic differential cross sections for He+H2O collisions

Abstract: Elastic and rotationally inelastic cross sections have been measured for He+H2O scattering at two collision energies, 66.3 and 99.0 meV, using the crossed molecular beam technique. The inelastic events are detected by time-of-flight analysis of the scattered He atoms. The data are converted to elastic differential cross sections and inelastic angular-dependent energy loss spectra in the center-of-mass system. They are compared with averaged, full close-coupling calculations of state-to-state cross sections for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
7
18
0
Order By: Relevance
“…26,27 In the case of He, very similar DCS results were obtained in Ref. 5, providing an independent check of our method.…”
supporting
confidence: 67%
“…26,27 In the case of He, very similar DCS results were obtained in Ref. 5, providing an independent check of our method.…”
supporting
confidence: 67%
“…The lighter systems, particularly that of He, have been the target of numerous theoretical investigations; [5][6][7] the heavier ones (that of Kr and Xe) are practically unknown. Except for He [8] and Ar, [9] accurate experimental characterizations are missing. We show that the systematic investigation of the five water-noble-gas systems, the study of variations of our observables along the series, and comparison with the behavior of analogous systems, prototypical of vdW, provide unique information on the strength and range of intermolecular forces and cast light on the nature and role of interaction components which add to the vdW forces.…”
mentioning
confidence: 97%
“…the well--depth and location of zero potential), assuming a Lennard--Jones (12,6) potential. Brudermann et al 3 presented measurements of differential cross sections for H2O+He elastic scattering and reported partially state--resolved inelastic angular dependent energy loss spectra, at two different collision energies. Capelletti et al 12,14 reported determination of the potential parameters for the isotropic component of the D2O--He and D2O-D2 interaction by elastic scattering studies.…”
Section: Introductionmentioning
confidence: 99%